The Levels of Joy in Muslims’ Celebrations: A Comparison between Eid and Weddings - Husain, Waqar; Zahoor, Kiren; Ijaz, Farrukh (el Harakah: Jurnal Budaya Islam, 2021)
The current study intended to analyze the levels of joy in religious festivals. It involved 387 Pakistani Muslims including men (n=143) and women (n=282). Data was collected through a specifically developed questionnaire in Urdu. The findings revealed that Pakistani Muslims enjoy their festivals at a very low degree and the levels of joy in Eid-ul-Fitr and Eid-ul-Adha remains significantly lower than the levels of joy in weddings.  The level of joy for Pakistanis during different festivals could not exceed 31 percent. The findings further revealed that, instead of being joyous, a little minority of the respondents felt sadness and tiredness while celebrating different festivals. Men had significantly higher levels of joy on Eid-Ul-Fitr and Eid-Ul-Adha as compared to women. Women had significantly higher levels of joy on close-relative’s wedding as compared to men. Unmarried had significantly higher levels of joy on friend’s wedding as compared to married.  Kajian kali ini bertujuan untuk menganalisis tingkat keceriaan pada hari raya keagamaan. Ini melibatkan 387 Muslim Pakistan termasuk pria (n=143) dan wanita (n=282). Data dikumpulkan melalui kuesioner yang dikembangkan secara khusus dalam bahasa Urdu. Temuan mengungkapkan bahwa Muslim Pakistan menikmati festival mereka pada tingkat yang sangat rendah dan tingkat kegembiraan di Idul Fitri dan Idul Adha tetap jauh lebih rendah daripada tingkat kegembiraan dalam pernikahan. Tingkat kegembiraan orang Pakistan selama festival yang berbeda tidak bisa melebihi 31 persen. Temuan lebih lanjut mengungkapkan bahwa, alih-alih gembira, sebagian kecil responden merasakan kesedihan dan kelelahan saat merayakan festival yang berbeda. Pria memiliki tingkat kegembiraan yang jauh lebih tinggi pada Idul Fitri dan Idul Adha dibandingkan dengan wanita. Wanita memiliki tingkat kegembiraan yang jauh lebih tinggi pada pernikahan kerabat dekat dibandingkan dengan pria. Belum menikah memiliki tingkat kegembiraan yang jauh lebih tinggi pada pernikahan teman dibandingkan dengan menikah.